IMPACT OF THE PINK OCTOBER IN THE MAMMOGRAPHIC SCREENING ADHERENCE IN A REFERENCE CENTER IN ONCOLOGY - Gomes, Douglas Soltau; Vazzoller, Poliana Ruhmke; Fernandes, Yuri Costa Farago; Gotardo, Bruna Aparecida; Ruhnke, Jocelito (Mastology, 2017)
Objective: To analyze the impact of Pink October in the mammographic screening adherence in a reference center in oncology. Methods: This is a cross-sectional, descriptive and retrospective study of a population of women who underwent mammographic screening in the years 2014, 2015 and 2016. Mammography reports were used for data collection. Comparing the months of October with the other months of the studied years, we observed if there were changes in the number of mammograms and in the proportion of mammograms Breast Imaging Reporting and Data System (BI-RADS) 3, 4 and 5. To verify statistical significance, the Z-score (95% confidence interval — CI95%) and the χ2 test (p<0.05) were used. Results: 105,698 mammograms were performed. There was a significant difference in the number of mammograms performed in October compared to the other months of the study. In addition, there was an absolute increase in the number of mammograms BI-RADS 3, 4 and 5; however, their proportion in the months of October did not presented difference in comparison to the other months. Conclusion: Population-based campaigns to prevent breast cancer appear to be effective in increase of demand for mammographic screening, possibly leading to an increase in the number of cancers discovered, allowing more women to receive timely treatment.